»Ein Gott und Vater aller«: exegetische Beobachtungen zum neutestamentlichen Monotheismus - Feldmeier, Reinhard (Early christianity, 2010)
The point of New Testament monotheism is not singularization of the divine. The confession of the one and unique God refers to the God who as Father of Jesus Christ selects and unites the followers as his community. Like other divine characteristics in the scriptures God's unity and uniqueness proves to be a communicative trait.